Parent post-traumatic growth after a child's critical illness - Yagiela, Lauren M.; Edgar, Camera M.; Harper, Felicity W. K.; Meert, Kathleen L. (Frontiers in Pediatrics, 2022)
Objective: Posttraumatic growth is the experience of a positive change after a traumatic event. Our objective is to characterize the factors associated with posttraumatic growth in parents after a child’s pediatric intensive care unit (PICU) admission. Study Design: A cross-sectional survey study examining posttraumatic growth and select independent variables in parents one year after a child’s ≥ 72 hour PICU admission for an acute illness or injury. The study was completed in parents of children discharge alive from a tertiary care PICU from January 1, 2017 to December 31, 2017. A mixed-effects linear regression model was built to evaluate the effect of posttraumatic stress, anxiety, depression, resiliency, family function, and child function on posttraumatic growth. Results: Eighty-two parents of 52 children discharged alive in 2017 completed the survey. Fifty-two percent were ≥35 years and 64.3% were mothers. Median age of their children was 2.8 years (IQR 0.5-11.3) with a median hospital stay of 12 days (IQR 6-20). Moderate-to-high levels of posttraumatic growth occurred in 67.1% of parents. Increased hospital length of stay (B coeff 0.85; p=0.004, 95% CI 0.27, 1.43) and parent posttraumatic stress symptoms (B coeff 1.04; p=0.006, 95% CI 0.29, 1.78) were associated with increased posttraumatic growth, and increased parent depression symptoms (B coeff -1.96; p=0.015; 95% CI -3.54, -0.38) with decreased posttraumatic growth. Conclusions: Longer child hospital stays and increased parent posttraumatic stress symptoms were associated with increased posttraumatic growth, while increased depression was associated with less posttraumatic growth. The impact of future PICU parent psychosocial interventions on parents may be best assessed using a dual outcome focused on both reducing negative mental health symptoms while concurrently promoting skills to facilitate parent adaptation and posttraumatic growth.